Puding bagi ibu hamil dan menyusui: kajian jenis dan konsentrasi tepung ubi jalar Cilembu - Anna Ingani Widjajaseputra; Maria Matoetina Suprijono; Theresia Endang Widoeri Widyastuti (AGROINTEK, 2026)
East Java is a major center of sweet potato production and has the potential to provide nutrients required by pregnant and breastfeeding women. Sweet potato flour-based food products, such as silky pudding, may serve as suitable supplementary foods for these groups. However, silky pudding is prone to quality deterioration due to syneresis. This study aimed to evaluate the effects of two types of Cilembu sweet potato (UJC) flour and their concentrations on the physicochemical and organoleptic properties of pudding. The two types of UJC flour differed in drying method, namely oven drying (M1) and foam-mat drying (M2), both applied at 55–60°C. The experiment was conducted using a nested factorial randomized block design. UJC flour concentration, consisting of 2%, 4%, 6%, and 8%, was nested within the flour type factor, with three replications. The dependent variables measured were starch content, reducing sugar content, sucrose content, syneresis, and mouthfeel preference. Data were analyzed using ANOVA at α = 5%, followed by the Least Significant Difference test at α = 5%. The type of UJC flour significantly affected the sugar content and syneresis of the pudding. Pudding prepared with oven-dried UJC flour (M1) had higher total sugar content and syneresis than pudding prepared with foam-mat-dried UJC flour (M2). Increasing the concentration of UJC flour, for both M1 and M2, significantly increased starch content while reducing the sugar and sucrose contents of the pudding. Syneresis was minimized by using foam-mat-dried UJC flour (M2). Based on the mouthfeel preference test, the recommended concentration for pudding intended for pregnant and breastfeeding women was up to 6% for oven-dried UJC flour (M1) and up to 4% for foam-mat-dried UJC flour (M2).